The Future Scenarios of Automation and Robot Implementation in the Manufacturing Industry - Azman, Nurul Afiqah; Ahmad, Nurazwa (Journal of Technology Management and Business, 2023)
Since 1983, manufacturing industry in Malaysia has embraced automation and robotics under the leadership of former Prime Minister, Tun Dr Mahathir Mohamad. Manufacturing companies in Malaysia have been encouraged to embrace automation and robotics as it offers many benefits to the country. However, the radical fluctuations in the dynamic manufacturing environment impose challenges for industries to keep up with the changes. Thus, this study was conducted to identify the STEEPV factors of social, technological, economic, environmental, politics and values that influence the adoption of full automation and robotics in the manufacturing industry. In addition, possible future scenarios for the implementation of full automation and robots were proposed as well. The research was conducted using STEEPV analysis where 50 managers from manufacturing companies responded to the distributed questionnaire. The result showed that economic sector had the greatest influence towards full automation and robots’ implementation in the manufacturing industry. In addition, the four scenarios predicted to occur for the next ten to fifteen years were ‘the dawn of smart manufacturing’, ‘inefficacious industry’, ‘ebb and flow’ and ‘obstreperous technological development’. The deliberate incorporation of automation and robots, aligned with strategic planning and a flexible policy framework, will not only boost productivity but also bolster the nation’s economic growth and global competitiveness. The manufacturing industry, in collaboration with the government, plays a pivotal role in realising the complete potential of these future scenarios, ensuring a prosperous and sustainable future for Malaysia. Keywords: Automation, robots, STEEPV, future scenario, manufacturing industry